Differential expression of sirtuin family members in the developing, adult, and aged rat brain - Sidorova-Darmos, Elena; Wither, Robert G.; Shulyakova, Natalya; Fisher, Carl; Ratnam, Melanie; Aarts, Michelle; Lilge, Lothar; Monnier, Philippe P.; Eubanks, James H. (Frontiers in Aging Neuroscience, 2014)
The sirtuins are NAD+-dependent protein deacetylases and/or ADP-ribosyltransferases that play roles in metabolic homeostasis, stress response and potentially aging. This enzyme family resides in different subcellular compartments, and acts on a number of different targets in the nucleus, cytoplasm and in the mitochondria. Despite their recognized ability to regulate metabolic processes, the roles played by specific sirtuins in the brain - the most energy demanding tissue in the body - remains less well investigated and understood. In the present study, we examined the regional mRNA and protein expression patterns of individual sirtuin family members in the developing, adult, and aged rat brain. Our results show that while each sirtuin is expressed in the brain at each of these different stages, they display unique spatial and temporal expression patterns within the brain. Further, for specific members of the family, the protein expression profile did not coincide with their respective mRNA expression profile. Moreover, using primary cultures enriched for neurons and astrocytes respectively, we found that specific sirtuin members display preferential neural lineage expression. Collectively, these results provide the first composite illustration that sirtuin family members display differential expression patterns in the brain, and provide evidence that specific sirtuins could potentially be targeted to achieve cell-type selective effects within the brain.